Item Response Theory Analysis: PROMIS® Anxiety Form and Generalized Anxiety Disorder Scale. (August 2022) - Liu, Wen; Dindo, Lilian; Hadlandsmyth, Katherine; Unick, George Jay; Zimmerman, M. Bridget; St. Marie, Barbara; Embree, Jennie; Tripp-Reimer, Toni; Rakel, Barbara
Little research has compared item functioning of the Patient-Reported Outcomes Measurement Information System (PROMIS ® ) anxiety short form 6a and the generalized anxiety disorder 7-item scale using item response theory models. This was a secondary analysis of self-reported assessments from 67 at-risk U.S. military veterans. The two measures performed comparably well with data fitting adequately to models, acceptable item discriminations, and item and test information curves being unimodal and symmetric. The PROMIS ® anxiety short form 6a performed better in that item difficulty estimates had a wider range and distributed more evenly and all response categories had less floor effect, while the third category in most items of the generalized anxiety disorder 7-item scale were rarely used. While both measures may be appropriate, findings provided preliminary information supporting use of the PROMIS ® anxiety short form 6a as potentially preferable, especially for veterans with low-to-moderate anxiety. Further testing is needed in larger, more diverse samples.